2023
DOI: 10.3390/ma16041601
|View full text |Cite
|
Sign up to set email alerts
|

Epoxy and Bio-Based Epoxy Carbon Fiber Twill Composites: Comparison of the Quasi-Static Properties

Abstract: In recent years, interest in sustainability has significantly increased in many industrial sectors. Sustainability can be achieved with both lightweight design and eco-friendly manufacturing processes. For example, concerns on the use of thermoset composite materials, with a lightweight design and a high specific strength, have arisen, since thermoset resins are not fully recyclable and are mainly petrol based. A possible solution to this issue is the replacement of the thermoset matrix with a recyclable or re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
(29 reference statements)
2
7
0
Order By: Relevance
“…Furthermore, no significant difference was observable between the mechanical behavior with respect to the two different epoxies, with similar results to Ref. [ 17 ], now considering a composite part.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, no significant difference was observable between the mechanical behavior with respect to the two different epoxies, with similar results to Ref. [ 17 ], now considering a composite part.…”
Section: Resultssupporting
confidence: 88%
“…As suggested by Mindermann et al [ 7 ], it is worth noticing that the resin system plays a significant role in the composite ecological performance, mainly when natural fibers are taken into account. Niutta et al [ 17 ] have compared quasi-static mechanical properties of petroleum- and bio-based epoxy resins and found no significant difference between them, apart from the GWP, which gives the designer the freedom to choose a bio-based epoxy system not only for ecological but also for technical reasons. La Rosa et al [ 11 ] have introduced an LCA comparison study between a bio-based polymer composite and a conventional glass/epoxy one.…”
Section: Introductionmentioning
confidence: 99%
“…The curves show also that the strains at failure for composites prepared with IB2 resin and ELIUM resin are larger compared to the composite prepared with the conventional epoxy resin. This behavior was also observed by Boursier et al [ 38 ] and Iadarola et al [ 13 ], who showed that the resins that have a higher bio content exhibit a larger deformation to failure both for flexural and tensile tests. Flexural tests conducted on composite laminates prepared with flax fibers also showed that the strain to failure increases for both composites prepared with IB2 and Elium resins.…”
Section: Resultssupporting
confidence: 80%
“…While the mechanical properties of bio-based resins appear promising, further research is necessary to compare them with commonly used epoxy resins in composite materials, ensuring safe design and structural integrity. Moreover, the suitability of these resins for vacuum infusion processes should be investigated due to potential viscosity issues [ 13 , 38 ]. Mechanical characterization of bio-based composite laminates is of utmost interest to universities and industries as it represents a promising approach for reducing the carbon footprint while employing existing production technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Among edible oils, options such as soybean [ 56 , 57 , 58 , 59 , 60 ], linseed [ 59 , 61 , 62 , 63 ] and hemp [ 60 , 64 , 65 ], stand out as potential sources for developing environmentally sustainable epoxy systems, as extensively analyzed in the comprehensive overview by Mustapha et al [ 66 ]. From triglyceride vegetable oils, such as coconut, soybean or palm oil, it is possible to obtain the glycerol , which is also commercially used to produce commercial resins [ 67 , 68 , 69 ] and proposed in the literature for the synthesis of new epoxy systems [ 38 , 70 , 71 ]. Furthermore, exploration into the integration of non-edible oils such as castor [ 72 , 73 ], karanja [ 37 ], and canola [ 74 ].…”
Section: Bio-epoxy Resinsmentioning
confidence: 99%